The developer's code what real programmers do - Cheung, Ka Wai (The pragmatic programmers, 2012)
You're already a great coder, but awesome coding chops aren't always enough to get you through your toughest projects. You need these 50+ nuggets of wisdom. Veteran programmers: reinvigorate your passion for developing web applications. New programmers: here's the guidance you need to get started. With this book, you'll think about your job in new and enlightened ways. The Developer's Code isn't about the code you write, it's about the code you live by. There are no trite superlatives here. Packed with lessons learned from more than a decade of software development experience, author Ka Wai Cheung takes you through the programming profession from nearly every angle to uncover ways of sustaining a healthy connection with your work. You'll see how to stay productive even on the longest projects. You'll create a workflow that works with you, not against you. And you'll learn how to deal with clients whose goals don't align with your own. If you don't handle them just right, issues such as these can crush even the most seasoned, motivated developer. But with the right approach, you can transcend these common problems and become the professional developer you want to be. In more than 50 nuggets of wisdom, you'll learn: Why many traditional approaches to process and development roles in this industry are wrong - and how to sniff them out. Why you must always say "no" to the software pet project and open-ended timelines. How to incorporate code generation into your development process, and why its benefits go far beyond just faster code output. What to do when your client or end user disagrees with an approach you believe in. How to pay your knowledge forward to future generations of programmers through teaching and evangelism. If you're in this industry for the long run, you'll be coming back to this book again and again.